Biological activity of apricot byproducts polyphenols using solid–liquid and infrared‐assisted technology. Issue 5 (29th April 2018) - Cheaib, Dina; El Darra, Nada; Rajha, Hiba N.; Ghazzawi, Iman El; Maroun, Richard G.; Louka, Nicolas
Abstract: This study compared the biological (antiradical, antioxidant, and antimicrobial) effects of phenolic compounds extracted from apricot pomace and kernels using solid–liquid (S/L) and infrared (IR) technology. IR pomace extract gave the highest polyphenolic content (10.8 mg GAE/g DM), flavonoid (6.3 mg CE/g DM), and tannin (3.6 mg/L) yields, exhibited the highest inhibitory activity against all tested gram‐positive and one gram‐negative bacterial strain ( Escherichia coli ) and had the highest antiradical capacity (AC) for DPPH and ABTS assays. As for total antioxidant activity, IR pomace gave the highest activity. High‐performance liquid chromatography (HPLC) permitted the identification and quantification of different phenolic molecules in apricot pomace (rutin, catechin, and epicatechin) and apricot kernels (caffeic and gallic acid) and which showed great polyphenol diversity in apricot byproducts. Results showed that IR technology gave better results in terms of the extraction efficiency and biological activity of the extracts compared with S/L ones. Practical applications: In recent years, the main research focus is on the use of green solvents and environment‐friendly technologies that diminish organic solvent use and energy consumption. Infrared‐assisted extraction technique is a novel technique composed of infrared lamp. In comparison with other conventional techniques, infrared is an easy, cheap, and effective technology which could be used to enhance the quality as well as quantity of polyphenols extracted from apricot byproducts.